Alpha and beta changes in anxiety in response to mass shooting related information. (February 2022) - O'Brien, Colin; Taku, Kanako
Abstract: The present study investigated how an individual's state anxiety may change before and after exposure to different types of information about mass shootings. Changes were analyzed as either alpha or beta changes; beta changes indicate a "recalibration" of one's anxiety as opposed to experiencing a direct change. A total of 364 participants from a midwestern university were randomly assigned to one of three conditions, in which they read either emotional information (a news article about mass shootings), unemotional information (statistics about mass shootings), or a filler article. Before and after reading these articles, participants responded to questions from the state portion of the State-Trait Anxiety Inventory. Analyses revealed that participants experienced alpha changes in anxiety after reading either article related to mass shootings, but not after reading the filler article. Furthermore, participants did not experience beta changes after reading any of the articles. These results demonstrate that information about mass shootings is likely to elevate anxiety levels regardless of its emotionality, and that these are direct changes as opposed to cognitive recalibrations. The results may be relevant for news sources reporting on mass shootings or professionals attempting to educate about mass shootings. Highlights: News coverage of mass shootings raises individuals' anxiety levels. There are two types of perceived changes: alpha and beta changes. Alpha changes, not beta changes, occur in response to news coverage. Changes are consistent whether news coverage is emotional or unemotional.